The effect of fibrin-stabilizing factor on the subunit structure of human fibrin - Martin L. Schwartz; Salvatore V. Pizzo; Robert L. Hill; Patrick A. McKee (The Journal of Clinical Investigation, 1971)
The formation of human fibrin from fibrinogen has been examined by polyacrylamide gel electrophoresis in sodium dodecyl sulfate, a method which separates a mixture of proteins on the basis of differences in molecular weight. It has been found that the plasma from a patient with a congenital deficiency of fibrin-stabilizing factor forms clots lacking the cross links among the α- and γchains found in normal, cross-linked human fibrin. The addition of purified fibrin-stabilizing factor or normal plasma to the deficient plasma results in extensive cross-linking of the chains. Thus, the fibrinogen in the fibrin-stabilizing factor deficient plasma appears to be normal and forms fibrin which contains dimeric, cross-linked γ-chains and polymeric, high molecular weight forms of α-chains. By the use of these electrophoretic methods, it has also been possible to develop a highly sensitive method for measuring the content of fibrin-stabilizing factor in plasma. This method depends upon the use of urea-treated fibrinogen, which is completely devoid of fibrin-stabilizing factor, but which forms the usual cross-linked subunits after conversion to fibrin by thrombin in the presence of fibrin-stabilizing factor. Images